(untitled) (Journal of Oriental Studies, 2019)
In article studying of religious views of Abu Hasr al-Farabi by the Kazakhstan scientists and studies abroad is considered. Modern scientists continue to explore creativity al-Farabi. At tne same time scientists are found in his writing support the basic doctrines of the religion of Islam. In article it is given in the chronological review from history of studying of religious views of Abu Nasr al-Farabi in world science and in Kazakhstan published in Soviet period and years of independence, the main concepts which are put forward in their contents are defined. The article is also considered life and works of the Second Teacher Abu Nasr al-Farabi referring to historical data in the Arab sources and the huge contribution of the scientist in a medieval Arab-Muslim civilization reveals. ritten monuments of Abu Nasr al-Farabi and the invaluable information about ancient Otyrar (Farab) reached us through bibliographic and encyclopedic works of medieval Arabicspeaking historians chroniclers are considered important sources for modern to a farabi’s studies. The role and importance of the state program which are carried out at the initiative of the First President of Kazakhstan "Cultural heritage", "The people – in a history stream", "Seven sides of the Great steppe" in return of the richest written monuments Abu Nasr al-Farabi to the Homeland – Kazakhstan are defined. Кеу words: Heritage of Al-Farabi, religion and philosophy, religious view, conception, research.